Marriage concerns: a study on single Singaporean graduates’ perceptions towards marriage - Shee, Xue Qi (2017)
The Singapore government has been grappling with the issues of ultra-low fertility rates and the threat of becoming an ageing population for the past few decades as it serves a threat to the nation’s future development. As the fundamental solution lies in encouraging Singaporeans to marry and reproduce more, the trend of delayed marriages and rise in singlehood among single Singaporean graduates needs to be addressed to better tackle such national concerns. Hence, this research paper aims to examine single Singaporean graduates’ perception towards marriage in order to shed light on the rising trend of delayed marriages and singlehood amongst this group through analyzing the research findings. It is observed that marriage, as a social institution, has gone through structural shifts but yet remains valued by the respondents despite delaying their marriage and remaining single due to the confluence of social factors.